2016
DOI: 10.1177/0023830916651097
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Success in Spatial Dialogue: The Impact of Functional Features and Dialogue Strategies

Abstract: 2 AcknowledgmentsWe thank the participating schools in Delmenhorst and Bremen for their collaboration, and our >10 student assistants for their invaluable help. This research was partially supported by a HWK fellowship (Hanse Institute for Advanced Studies, Delmenhorst, Germany) awarded to Kenny Coventry, and by DFG funding for SFB/TR8 Spatial AbstractThis paper addresses the impact of dialogue strategies and functional features of spatial arrangements on communicative success. To examine the sharing of cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Figure 7 from dialogue D1 between turns [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] shows that the distinction between information givers and information receivers [24] is difficult to maintain in dialogues that transition to clarification as it is not clear when their roles change or which participant in the clarification dialogue has more or less information at any of these points. In turn 14 P1 is the information giver but in turn 17 they are the information receiver and there is no change of the FoR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 from dialogue D1 between turns [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] shows that the distinction between information givers and information receivers [24] is difficult to maintain in dialogues that transition to clarification as it is not clear when their roles change or which participant in the clarification dialogue has more or less information at any of these points. In turn 14 P1 is the information giver but in turn 17 they are the information receiver and there is no change of the FoR.…”
Section: Resultsmentioning
confidence: 99%
“…More recent research on spatial dialogue has studied locative descriptions. For example, [28] examined communicative success in a task where one participant had to describe how to arrange and orient a set of objects in a dolls house and their partner had to furnish it based on these descriptions. 4 They found that a number of factors affected communication success, including: (a) the functional features of the spatial arrangement of the furniture (e.g., did the target orientation of a chair relative to a table align with expected/canonical arrangement of chairs and tables), (b) previous task experience, and (c) dialogue features such as description length and the inclusion of orientation information.…”
Section: Frames Of Referencementioning
confidence: 99%
“…Perceptual grounding and generating descriptions are minimal elements of human communication about shared environments (Tenbrink et al., 2017). Linking phrases to perception in both directions is a strength of our approach, as typical models cover only either production or comprehension (Pickering & Garrod, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The listener identifies objects or events in his environment that the speaker talks about, perceptually grounding them. Imagine, for example, two young siblings playing with a dollhouse (Tenbrink, Andonova, Schole, & Coventry, 2017). The sister describes to her brother a bed in the dollhouse, linking her perceptual experience to language.…”
Section: Introductionmentioning
confidence: 99%